1998
DOI: 10.1074/jbc.273.12.6656
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic Regulation of the Zinc Finger Transcription Factor YY1, a Repressor of Muscle-restricted Gene Expression

Abstract: Regulated proteolysis has been postulated to be critical for proper control of cell functions. Muscle development, in particular, involves a great deal of structural adaptation and remodeling mediated by proteases. The transcription factor YY1 represses muscle-restricted expression of the sarcomeric ␣-actin genes. Consistent with this repressor function of YY1, the nuclear regulator is down-regulated at the protein level during skeletal as well as cardiac muscle cell differentiation. However, the YY1 message r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 42 publications
3
54
0
Order By: Relevance
“…Adamowicz and co-workers [47] also reported that a mutation in the Sp1 binding site of the bovine leptin gene affects its expression level. The presence of a G allele of this SNP (rSNP4) created a binding site for the zinc finger nuclear protein, YY1 (Yin Yang 1), also known as NF-E1, UCRBP or CF1, which is known to have fundamental roles in repressing and activating a diverse group of promoters; it not only initiates transcription but also activates or represses it [48,49]. YY1 is also shown to repress muscle specific expression of sarcomeric alpha-actin and c-myc genes [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adamowicz and co-workers [47] also reported that a mutation in the Sp1 binding site of the bovine leptin gene affects its expression level. The presence of a G allele of this SNP (rSNP4) created a binding site for the zinc finger nuclear protein, YY1 (Yin Yang 1), also known as NF-E1, UCRBP or CF1, which is known to have fundamental roles in repressing and activating a diverse group of promoters; it not only initiates transcription but also activates or represses it [48,49]. YY1 is also shown to repress muscle specific expression of sarcomeric alpha-actin and c-myc genes [49].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a G allele of this SNP (rSNP4) created a binding site for the zinc finger nuclear protein, YY1 (Yin Yang 1), also known as NF-E1, UCRBP or CF1, which is known to have fundamental roles in repressing and activating a diverse group of promoters; it not only initiates transcription but also activates or represses it [48,49]. YY1 is also shown to repress muscle specific expression of sarcomeric alpha-actin and c-myc genes [49]. Walowitz and co-workers also reported that calpains and the 26 S proteasome are involved in YY1 stability in rat muscle indicating that myogenic transcription may be inactivated by developmentally regulated proteolysis to promote muscle development.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, in response to di erent stimuli these proteins may be subject to degradation by either calpain or the proteasome. An example of this dual regulation was shown recently in myoblasts where the transcription factor YY1 was degraded by calpain during skeletal muscle cell di erentiation, and by the proteasome in response to serum starvation (Walowitz et al, 1998). As discussed above, a considerable body of evidence has accumulated showing that RB and p107 function, although partially overlapping, may also be divergent.…”
Section: Discussionmentioning
confidence: 90%
“…Reported calpain substrates include cytokines, cytoskeletal-associated proteins, enzymes, including focal adhesion kinase (Cooray et al, 1996) and protein kinase C (Croall and Demartino, 1991;Eto et al, 1995), and the transcriptional activators c-fos, c-Jun, YY1, and p53 (Hirai et al, 1991;Kavita and Mizel, 1995;Walowitz et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation